PEMBUATAN PAPAN PARTIKEL DARI BUNGKIL JARAK KEPYAR (Ricinus communis L.) DENGAN PERLAKUAN PENDAHULUAN STEAM EXPLOSION - Ika Amalia Kartika dan Herdiarti Desti (E-Jurnal Agro-Industri Indonesia) (E-jurnal Agro-Industri Indonesia, 2015)
ABSTRACT Binderless particleboard production from castor cake meal is developed to overcome the limitation of wood in construction industry and to solve the environmental problem because of emission from urea formaldehide (UF) and phenol formaldehide (PF). The steam explosion method can be used to denaturate the protein of castor cake meal which can increase the mechanical properties of particleboard. Particleboard production was carried out by hot pressing at different temperatures and pressures. This research aimed to determine the effect of pressing temperature and pressure on the physical and mechanical properties of the particleboard, and to obtain the optimum pressing temperature and pressure on particleboard production from castor cake meal. The physical and mechanical properties of particleboards were tested according to JIS A 5908:2003. Generaly, the density and the moisture content of particleboard met JIS A 5908:2003. Statistical analysis showed that pressing temperature affected moisture content, water absorption and MOE whereas pressing pressure affected moisture content and water absorption. The regression analysis showed that the optimum pressing temperature and pressure to produce the particleboard from castor cake meal were respectively 160oC and 160 kgf/cm2 with density of 0.85 g/cm3, moisture content of 5.05%, water absorption of 124.54%, thickness swelling of  20%, MOE 256.65 kgf/cm2 and MOR 4.73 kgf/cm2.   Keywords: Castor cake meal, modulus of rupture, modulus of elasticity, particleboard, steam explosion